2020
DOI: 10.4317/medoral.23281
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of gap between abutment and fixture in dental conical connection implants. A focused ion beam SEM observation

Abstract: Background The aim of the authors was to examine the abutment-fixture interface in Morse-type conical implants in order to verify gaps at this level using a new microscopical approach. Material and Methods In this in vitro study, 20 abutment-fixture complexes were prepared by sectioning (longitudinal and cross-sectional to the long axis) with a microtome and then with a focused ion beam (FIB). This is a micrometric machine tool that uses galli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 15 publications
0
1
0
1
Order By: Relevance
“…There are divergences in the literature regarding the influence of the diameter and shape of the dental implant on primary stability. Researchers evaluated the primary stability of 60 implants divided into 3 groups with different geometries, and it was observed that there was no statistical difference between cylindrical implants and conical implants [13,14]. These data are relevant to the results of the present work.…”
Section: Discussionmentioning
confidence: 52%
“…There are divergences in the literature regarding the influence of the diameter and shape of the dental implant on primary stability. Researchers evaluated the primary stability of 60 implants divided into 3 groups with different geometries, and it was observed that there was no statistical difference between cylindrical implants and conical implants [13,14]. These data are relevant to the results of the present work.…”
Section: Discussionmentioning
confidence: 52%
“…Os pesquisadores avaliaram a estabilidade primária de 60 implantes divididos em 3 grupos com geometrias diferentes, e observaram que não houve diferença estatística entre implantes cilíndricos e implantes cônicos. 13,14 Esses dados são relevantes para os resultados do presente trabalho. Os resultados do presente trabalho mostraram que independente do diâmetro do implante, não há diferença significativa no índice ISQ entre os dois grupos.…”
Section: Discussionunclassified